Motivated Beliefs & Anticipation of Uncertainty Resolution: A Note - Alisher Batmanov; Idaliya Grigoryeva (Institute for Replication (I4R), 2023)
Drobner (2022) examines the effect of manipulating experimental subjects' expectations about uncertainty resolution in learning about their performance on their belief updating patterns in an ego-relevant domain. In their preferred empirical specification, the author finds that individuals update their beliefs optimistically as they exhibit a higher belief adjustment in response to good compared to bad news only when they do not expect resolution of underlying uncertainty about their performance in an IQ test and neutrally when they know they will find out their relative performance at the end of the experiment. First, we reproduce the all of the paper's findings without identifying any coding errors. Second, we test the robustness of the results to (1) adding individual covariates and (2) excluding subjects who exhibit a fundamental error in their belief updating from the analysis. We find no substantial changes in the main coefficients of interest with the inclusion of demographic variables in the analysis, consistent with demonstrated balance in covariates between the two experimental groups. Yet, several of the main estimates lose statistical significance and change from conservatism (under-updating) to over-inference (over-updating) in some conditions on the subset of participants excluding those who exhibit fundamental errors in belief updating.
Keywords: 330